Answer:
1: 64x4 - 400x3 + 719x2 - 300x + 31
2: 8x2 -25x +7
Explanation:
1: Using A=8x2 – 25x + 7, B=8x2– 25x + 11, C=10x2 – 25x + 7
Let's first compute A2:
A2 = (8x2 - 25x + 7)^2 = (8x2 - 25x + 7)*(8x2 - 25x + 7)
= 64x4 - 200x3 + 56x2 - 200x3 + 625x2 - 175x + 56x2 - 175x + 49
= 64x4 - 400x3 + 737x2 - 350x + 49
Now, let's compute (B + C):
B + C = 8x2– 25x + 11 + 10x2 – 25x + 7 = 18x2 - 50x + 18
Finally, we can do A2 - (B + C):
A2 - (B + C) = 64x4 - 400x3 + 737x2 - 350x + 49 - (18x2 - 50x + 18)
= 64x4 - 400x3 + 719x2 - 300x + 31
2: Using A = 3x – 4, B = x + 7, C = x2 + 2
A2 = (3x-4)^2 = (3x-4)*(3x-4) = 9x2 - 12x - 12x + 16 = 9x2 - 24x + 16
B + C = x + 7 + x2 + 2 = x2 + x + 9
A2 - (B + C) = 9x2 - 24x + 16 - (x2 + x + 9) = 8x2 -25x +7